If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.08(x + 50) + -0.16x = 0.12(50) Reorder the terms: 0.08(50 + x) + -0.16x = 0.12(50) (50 * 0.08 + x * 0.08) + -0.16x = 0.12(50) (4 + 0.08x) + -0.16x = 0.12(50) Combine like terms: 0.08x + -0.16x = -0.08x 4 + -0.08x = 0.12(50) Multiply 0.12 * 50 4 + -0.08x = 6 Solving 4 + -0.08x = 6 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -0.08x = 6 + -4 Combine like terms: 4 + -4 = 0 0 + -0.08x = 6 + -4 -0.08x = 6 + -4 Combine like terms: 6 + -4 = 2 -0.08x = 2 Divide each side by '-0.08'. x = -25 Simplifying x = -25
| (x^-4y^2/x^4y^-3)^-2 | | 2y+12x=-6 | | x^2=-76 | | (N^2-4)=0 | | 7.2(-8.1)+56.14= | | 6h+1+49+82=180 | | 0.05x+0.1(36-x)=2.55 | | 4x+3(x+2)=-36 | | 4w^2-12w+9=0 | | z(2+i)=1-4i | | 8x+5-5x=20 | | (y-7)+y=39 | | 3v^2-5v=0 | | 3/4-3/8/2/3 | | -8/-3= | | 2/6-6=3x-3/15 | | 15/8=5v | | 5m+3m=40 | | Ln(x-3)=2.5 | | 9x+4=8x+12 | | Z+(1+3i)=2-5i | | -3m+2(2+2m)=13 | | 7x+2=3x+7 | | 9-4x^4=0 | | 7x-4*(2x-1)+7=-2(1-2x)+3 | | 4x^2=82 | | -20=5/6*x | | logx(x-21)=2 | | 3x*2x^6w^6*8w^4= | | 4(m-3)=12-2 | | logx(x-21)=7 | | 4y-3y^2-3xy=0 |